2018
DOI: 10.1002/hbm.24281
|View full text |Cite
|
Sign up to set email alerts
|

Language network measures at rest indicate individual differences in naming decline after anterior temporal lobe resection

Abstract: While anterior temporal lobe (ATL) resection is an effective treatment for temporal lobe epilepsy, surgery on the dominant hemisphere is associated with variable decline in confrontation naming. Accurate prediction of naming impairment is critical to inform clinical decision making, and while there has been some degree of success using task-based functional MRI (fMRI) paradigms, there remains a growing interest in the predictive utility of resting-state connectivity as it allows for relatively shorter scans wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 76 publications
3
36
0
Order By: Relevance
“…Clinical applications of resting state fMRI to epilepsy surgery include preoperative functional mapping to help guide surgical planning (Doucet, Pustina, et al, 2015; Liu et al, 2009; Mitchell, Hacker, & Breshears, 2013) and identifying prognostic markers of individual patients' relevant clinical outcomes after surgery (Boerwinkle, Mohanty, Foldes, et al, 2017; He et al, 2017; Negishi, Martuzzi, Novotny, Spencer, & Constable, 2011). There are limited data on the ability of resting state fMRI to predict neurocognitive outcomes after surgery, including language and memory (Audrain, Barnett, & McAndrews, 2018; Doucet, Rider, & Taylor, 2015; McCormick, Quraan, Cohn, Valiante, & McAndrews, 2013). In addition, others have shown that the best predictive model of verbal fluency change following dominant anterior temporal lobectomy was one that combined all three imaging modalities: task fMRI, resting state fMRI, and DTI (Osipowicz, Sperling, Sharan, & Tracy, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical applications of resting state fMRI to epilepsy surgery include preoperative functional mapping to help guide surgical planning (Doucet, Pustina, et al, 2015; Liu et al, 2009; Mitchell, Hacker, & Breshears, 2013) and identifying prognostic markers of individual patients' relevant clinical outcomes after surgery (Boerwinkle, Mohanty, Foldes, et al, 2017; He et al, 2017; Negishi, Martuzzi, Novotny, Spencer, & Constable, 2011). There are limited data on the ability of resting state fMRI to predict neurocognitive outcomes after surgery, including language and memory (Audrain, Barnett, & McAndrews, 2018; Doucet, Rider, & Taylor, 2015; McCormick, Quraan, Cohn, Valiante, & McAndrews, 2013). In addition, others have shown that the best predictive model of verbal fluency change following dominant anterior temporal lobectomy was one that combined all three imaging modalities: task fMRI, resting state fMRI, and DTI (Osipowicz, Sperling, Sharan, & Tracy, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested solely an expressive component of the language by utilizing the word generation paradigm, which has also been used by other groups for determining language networks in epilepsy patients (28). Paradigms related to semantic aspects of language, such as picture/auditory naming or semantic decision tasks are also widely used (31, 32, 4245). Different fMRI tasks, which engage diverse aspects of language, may show either equal or various lateralization patterns (28, 31, 32, 4245).…”
Section: Discussionmentioning
confidence: 99%
“…Paradigms related to semantic aspects of language, such as picture/auditory naming or semantic decision tasks are also widely used (31, 32, 4245). Different fMRI tasks, which engage diverse aspects of language, may show either equal or various lateralization patterns (28, 31, 32, 4245). They may also have different predictive value for postoperative naming decline in epilepsy surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 Other recent work has shown the ability of preoperative resting state fMRI and white matter connectome markers to predict postoperative cognition, particularly in relation to language. 46 …”
Section: Lesion Detection and Disease Biotyping Techniquesmentioning
confidence: 99%